Rocky Mountain Man - Hart, Jillian (New York Harlequin Books, 2005)
A big and burly mountain man, a half breed some said, he seemed not unlike the bears he'd saved Betsy Hunter from- wild, powerful, a force of nature, but as she tended the wounds this loner had suffered because of her, Betsy could see that he was gentle, too, with an artist's soul. And thought he's professed to like the lonely existence he'd carved for himself in the wilds of Montana, Betsy knew otherwise. There was no doubt that in Duncan Hennseesy, she'd found her true mate for life. But could she pierce the dark cloud of his past--and show him a brighter future in her arms?
Keywords: Man-woman relationships